2007
DOI: 10.1518/106480407x255198
|View full text |Cite
|
Sign up to set email alerts
|

What Older Adults Can Teach Us About Designing Better Ballots

Abstract: FEATURE AT A GLANCE: In this article, we examine the interplay between electronic voting technology machine types (touchscreen vs. touchscreen + keypad) and ballot designs (full ballot vs. one office per page) that together comprise the interface to which voters are exposed. Using a gerontological approach, we show that determining the most usable system for voters with the most limited capabilities (in this study, older participants) also corresponded to higher performance across groups (younger part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Although they did note a relatively large difference in ballot completion times between their DRE and lever voting machines (DREs were more efficient), as of 2010 New York state became the last U.S. state to abandon lever voting machines, making lever machines defunct. In their second experiment, Everett et al (2008) corroborate Jastrzembski and Charness's (2007) findings that direct navigation models in the voting context, though more efficient, are likely to produce a decrease in voting system effectiveness and that the disparity has the potential to be much greater for older adults.…”
Section: Introductionsupporting
confidence: 58%
“…Although they did note a relatively large difference in ballot completion times between their DRE and lever voting machines (DREs were more efficient), as of 2010 New York state became the last U.S. state to abandon lever voting machines, making lever machines defunct. In their second experiment, Everett et al (2008) corroborate Jastrzembski and Charness's (2007) findings that direct navigation models in the voting context, though more efficient, are likely to produce a decrease in voting system effectiveness and that the disparity has the potential to be much greater for older adults.…”
Section: Introductionsupporting
confidence: 58%
“…In addition, research has shown how redundant coding of information through tactile feedback can be used to further enhance accessibility (e.g., Lederman & Hamilton, 2002) and should be leveraged in the design of voting interfaces. These features are important because making things more accessible will also likely simplify the voting process for the rest of the population (Jastrzembski & Charness, 2007).…”
Section: Reversibility Of Actionsmentioning
confidence: 99%
“…Other sources of problems include symbols used to indicate political parties, which can vary from using symbols to various animals. Instructions which are vague or misleading (such as asking the voter to vote for one, when there are multiple candidates together) can lead to confusion, with the resulting errors and problems (Jastrzemski and Charness, 2007;Alvarez, Sinclair, and Hasen, 2006;Alvarez, 2002). Voting should also be a relatively quick process, especially if there are not an excessive number of races requiring votes at the same time.…”
Section: Assessment Of Usabilitymentioning
confidence: 99%